Distribution of Fatty Acids in A Seedling Almond Population and Their Mutual Relationships - ÇELIK*, FERIT; BALTA†, FIKRI; DOGAN, ADNAN; JAVIDIPOUR‡, I.; KAZANKAYA†, AHMET (Asian Journal of Chemistry, 2024)
This paper deals with determining kernel fatty acid contents based on oil distribution in a seedling almond population consist of 90 seedling trees from Turkey and mutual relationships among fatty acids. Almond population was divided into three groups based on the range of fat contents. Genotypes averagely contained 6.70 % palmitic acid, 0.57 % palmitoleic acid, 1.78 % stearic acid, 72.83 % oleic acid, 18.03 % linoleic acid, 0.15 % linolenic acid and 0.39 % myristic acid. In addition, they had 91.58 % unsaturated fatty acid content, 8.87 % saturated fatty acid content and 10.32 unsaturated/saturated ratio. Findings of this study indicate that contents of oleic and linoleic acids were influenced by the range of oil in the seedling population.